Siting Multiple Observers for Maximum Coverage: An Accurate Approach - Romero, Luis F.; Tabik, Siham; Cervilla, Antonio R. (My University, 2015)
The selection of the minimal number of observers that ensures the maximum visual coverage over an area represented by a digital elevation model (DEM) have great interest in many elds, e.g., telecommunications, environment planning, among others. However, this problem is complex and intractable when the number of points of the DEM is relatively high. This complexity is due to three issues: 1) the di culty in determining the visibility of the terrain from one point, 2) the need to know the visibility at all points of the terrain and 3) the combinatorial complexity of the selection of observers. The recent progress in total-viewshed maps computation not only provides an e cient solu- tion to the rst two problems, but also opens other ways to new solutions that were unthinkable previously. This paper presents a new type of cartography, called the masked total viewshed map, and provides optimal solutions for both sequential and simultaneous observers location.